Investigating adolescent psychological wellbeing in an educational context using PISA 2018 Canadian data - Liu, Yan; Maltais, Natasha S.; Milner-Bolotin, Marina; Chachashvili-Bolotin, Svetlana (Frontiers in Psychology, 2024)
Introduction Adolescent psychological wellbeing has been identified as an important public health priority and one of the major challenges facing young people. However, few studies have examined the wellbeing of Canadian adolescents nationwide in the past decade, and even fewer have focused specifically on immigrant adolescents. This study aims to investigate Canadian adolescent psychological wellbeing (PWB) via nationally representative data from the Programme for International Student Assessment (PISA) 2018. We explored what social and educational factors were critical in predicting Canadian adolescents' PWB, how adolescents from immigrant families differed from their non-immigrant peers in their wellbeing, and how adolescents' PWB was related to their academic performance. Methods A total of 22,651 Grade 8 Canadian students who participated PISA 2018 were included in this study (mean age of 15; 49.9% female; 26% immigrant students). Mixed effects modeling was adopted for data analysis. Results Our results showed that various social and educational factors were associated with adolescent PWB, but these relationships varied depending on which aspect of PWB was examined. Immigrant adolescents were shown to have higher levels of PWB when student attitudes toward immigrants were more positive. Additionally, most aspects of PWB were important for achievement performance. Discussion It is important to develop healthy and supportive school and disciplinary climates that foster students' sense of belonging. To further support the PWB of immigrant adolescents, educators can implement activities and integrate learning materials on cultural diversity into curricula, encouraging students to develop positive attitudes toward immigrants. Our findings on the PWB of Canadian adolescents could provide valuable insights for other countries with diverse populations, particularly those with significant immigrant communities.